Uji Tingkat Kesukaan dan Kandungan Zat Gizi Protein dan Kalsium pada Nugget Ikan Dero (Stolephorus indicus E.) - Anugrah, Riva Mustika; Nurul Fajriyah, Salisa Kinanti (Universitas Muhammadiyah Semarang, 2024)
A fish nugget is a processed product made from fish meat that is popular among all levels of society because of its delicious taste and practical presentation. The nutritional content of fish nuggets is high in protein and can be enriched with calcium. Dero fish is a local fish that is high in protein and calcium. This research aimed to determine the level of preference and nutritional content of protein and calcium in dero fish (Stolephorus indicus E.) nugget. This research uses an experimental design. The treatment carried out is by making fish nugget with the basic ingredients of dero fish. The treatment will be carried out by making 3 different formulations with fish meat weight ratios: the weight of white bread F1 (80% : 20%), F2 (70% : 30%), and F3 (60% : 40%). Then a preference level test was carried out followed by a protein and calcium nutritional content test. The most preferred formulation based on the liking level test was formula 2 with a color percentage value of 68.6%, texture 69.3%, aroma 67.3% and taste 80.6%. The nutritional content of protein and calcium in dero formula 2 fish nugget is 11.73% protein and 326.6 mg calcium.